Performance evaluation of a manual and a motor-operated maize seeder: Performance test of power operated maize seeder (Journal of the Bangladesh Agricultural University, 2019)
A motor-operated maize seeder was designed and fabricated. The performance of the seeder was tested in laboratory and compared with a manual-operated seeder. Hybrid maize seed variety, Sunshine NK40 by Syngenta, was used for the performance test of the seeder during January to April/2017. The two seeders, manual-operated and motor-operated, provided an average seed spacing of 22.48 cm and 20.94 cm, respectively, while the standard seed spacing for maize is 20 cm. The seed spacing of the motor-operated seeder varied from the standard value because of the trapping of seed between the seed hopper and metering device. The missing rate of the manual seeder was 13.2% while the motor-operated seeder provided a missing rate of 5.9%. Due to constant forward speed, the motor-operated seeder resulted in 2.3 times lesser missing rate than the manual seeder. The seed rate of the manual- and motor-operated seeder was found to be 30 kg/ha and 25.7 kg/ha, respectively, although both the seeders were calibrated to maintain a constant seed rate of 25 kg/ha. The field capacity and field efficiency of the existing manual seeder was found 0.128 ha/h and 76.65%, respectively, whereas the field capacity and field efficiency of the motor-operated seeder was found 0.135ha/h and 74.76%, respectively. The motor-operated seeder has a limitation of time loss during turning and the required time loss resulted in low field capacity and field efficiency. Break-even analysis shows that at the yearly use of 0.23 hectares, the operation cost of manual seeder and hand application method were the same. Therefore, manual seeder will be beneficial to the farmers when the annual use exceeds 0.23 hectares of land. Compared to manually-operated seeder, the motor-operated seeder can reduce seed requirement by reducing missing rate and save labor and time of operation if the time loss during turning can be minimized.J. Bangladesh Agril. Univ. 17(2): 251–257, June 2019